2019
DOI: 10.1111/bjd.18361
|View full text |Cite
|
Sign up to set email alerts
|

Complete skin clearance and Psoriasis Area and Severity Index response rates in clinical practice: predictors, health‐related quality of life improvements and implications for treatment goals

Abstract: Summary Background Psoriasis Area and Severity Index (PASI) 90 is suggested to be the new standard endpoint for randomized controlled trials of biologics for psoriasis, whereas treatment guidelines often still refer to PASI 75. Objectives To analyse in a real‐world setting: firstly, what factors are associated with higher levels of treatment response to biologics; secondly, the health‐related quality of life gains associated with different response levels in clinical practice. Methods Biologically naïve patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 33 publications
3
27
0
6
Order By: Relevance
“…The higher absolute baseline PASI was statistically associated with the higher PASI percentage response for PASI-75 and 90 at week 16, as recently reported for TNF-a, IL12-23 and IL-17 inhibitors. 4 As in clinical trials, 5 risankizumab showed no significant safety signals, with only one patient developing upper respiratory tract infection, without discontinuation of treatment. None of our patients was infected with SARS-COV2, including the three patients having contact with infected subjects.…”
mentioning
confidence: 95%
“…The higher absolute baseline PASI was statistically associated with the higher PASI percentage response for PASI-75 and 90 at week 16, as recently reported for TNF-a, IL12-23 and IL-17 inhibitors. 4 As in clinical trials, 5 risankizumab showed no significant safety signals, with only one patient developing upper respiratory tract infection, without discontinuation of treatment. None of our patients was infected with SARS-COV2, including the three patients having contact with infected subjects.…”
mentioning
confidence: 95%
“…Optimal response criteria have been discussed widely, currently with focus on absolute values, either single values of PASI, Physician Global Assessment (PGA), or body surface area (BSA) (14,15,(36)(37)(38) or composite outcomes (39). We provide here evidence of the importance of high clearance on stability and long-term outcome of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of QoL using oral psoralen and daylight has been described for patients with severe psoriasis experiencing a higher QoL impairment (33) than the MF patients of this study. Of note, in psoriasis and atopic dermatitis, impairment, and improvement of QoL are linked to body surface extension of disease (34)(35)(36)(37)(38). Moreover, psoriasis patients with therapyinduced improvement but not complete clearance of skin may still suffer from substantial QoL impairment (34).…”
Section: Discussionmentioning
confidence: 99%